Anaesthetic Management of Patients for Brachytherapy in Radiation Suite - Aamir Bashir, Muhammad Naveed Azhar, Muhammad Azam (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Cervical cancer is one of the leading sites for cancer in female patients and brachytherapy remains one of the treatment modality for it. Anaesthetic services are required in certain cases. Anaesthesia services outside operating room pose challenges for anaesthesiologists due to remote access need for slave monitors etc. Aim: To evaluate the outcome of different anaesthetic techniques in female patients undergoing cervical brachytherapy procedures in radiotherapy department. Methods: This retrospective cross-sectional analysis conducted at a tertiary care cancer centre of Shaukat Khanum Memorial Trust Lahore. Anaesthetic details of all female patients planned for brachytherapy over a time period of three years from 2016 to 2018 was recorded. The subjects were female patients for the given procedure. Their mean age in years, ASA status, anaesthetic technique either General anaesthesia or Spinal anaesthesia in terms of patient number and percentage of total patients for either, any complication related to anaesthetics was recorded. Chi square test was applied to see any correlation between anaesthetic technique and complications. Results: There were 87 female patients in this research having mean age of 51±15 years. Regarding ASA physical status, 27(31%) of ASA status II while 60(69%) patients of ASA status III. General anaesthesia was given to 33(38%) patients, while 54(62%) patients received spinal anaesthesia. Overall, complications rate remained 7% and it was less in spinal anaesthesia (2%) as compared to general anaesthesia (8%) with statistically significant p-value of 0.001 Conclusions: We concluded that cervical brachytherapy can be safely conducted under spinal anaesthesia in radiation suite. Keywords: Brachytherapy, spinal anaesthesia, general anaesthesia, anaesthesia outside OR.